Spanish Republican Deportees Victims of Medical Experiments in Nazi Camps - González López, Esteban; Ríos Cortés, Rosa; Cuerda, Esther (Hispania Nova, 2024)
In some Nazi camps, thousands of inmates were used as guinea pigs for military and racial purposes such as cold-water immersion, forced drinking of seawater, high altitude exposure, testing of vaccines and drugs against infectious diseases, and searching for the best methods to sterilize men and women. These atrocities were carried out without any regard for the subjects. The experiments conducted by Nazi doctors in Auschwitz, Dachau or Ravensbrück are very well known, but not so much those in Mauthausen. By examining memoirs of survivors and documents from different international archives, we have gathered information on 34 Spanish republican deportees who were victims of medical experiments in some Nazi camps such as Mauthausen (Austria), Dachau, Buchenwald, and Ravensbrück (Germany).The aim of this paper is to bring some of their stories to light and remember that there were also Spanish people among the victims of Nazi medical experiments.
Keywords: nazi medical experiments; nazi camps; nazi doctors; spanish republican deportees; holocaust